Changing the Prenatal Care Paradigm to Improve Breastfeeding Outcomes. Issue 3 (May 2020) - Spatz, Diane L.
Abstract : A new paradigm for teaching families about benefits of breastfeeding is needed to help all mothers meet their breastfeeding goals. During prenatal care, breastfeeding should be discussed at every visit. Our breastfeeding expert, Dr. Spatz, describes the new paradigm and how to incorporate it into clinical practice.